Association of Circular RNAs levels in blood and Essential Hypertension with Carotid Plaque - Qian, Haiyan; Zhang, Zebo; Tao, Zhenbo; Xie, Yanqing; Yin, Yueqi; He, Wenming; Zhang, Lina (Clinical and experimental hypertension (1993), 2023)
As one of the essential hypertension (EH)-mediated target organ damage, carotid plaque is a crucial subclinical precursor for cardiovascular events. Therefore, it is vital to identify the risk factors and pathogenesis for EH with carotid plaque. Based on our previous microarray analysis, we selected four circRNAs as the candidate circRNAs and detected their expression levels in blood of 192 subjects (64 healthy controls, 64 EH patients, and 64 EH patients with carotid plaque) by qRT-PCR analysis. The regulatory mechanism of circRNAs involved in carotid plaque was predicted by bioinformatics analysis. The level of hsa_circ_0124782 increased significantly and the levels of hsa_circ_0131618 and hsa_circ_0127342 decreased significantly in the EH group and EH with carotid plaque group compared with the control group (P < .05). Functional enrichment analysis showed that three circRNAs might be implicated in pathogenesis for carotid plaque. Our study revealed the relationship between three circRNAs and carotid plaque, suggesting that they may serve as potential biomarkers for EH with carotid plaque.